Investigating the Frequency of Symptomatic Extracranial Artery Stenosis in Patients with Ischemic Stroke Admitted to Imam Khomeini Hospital of Urmia in 2011–2012 and Its Relationship with Cardiovascular Risk Factors - Mosarrezaii, Arash (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: Stroke is one of the two leading causes of mortality worldwide and leads to 9.7% of the world’s total deaths. Identifying risk factors that increase the likelihood of stroke or the factors that are associated with its occurrence may have an important role in reducing this disease. The aim of this study was to determine the frequency of symptomatic extracranial artery stenosis in patients with ischemic stroke (IS) admitted in Imam Khomeini Hospital of Urmia in 2011–2012 and its relationship with cardiovascular risk factors. Materials and Methods: This is a descriptive-analytic study in which 149 patients admitted in the neurology department of Imam Khomeini Hospital in Urmia, who had been diagnosed with ischemic cerebrovascular accident (CVA), were examined by a neurologist and the findings of disease record, examination, computed tomography scan, and color Doppler ultrasonography were compared, and the patients with symptomatic extracranial stenosis were entered into this study and a pre-prepared questionnaire was completed about their condition. Data were analyzed using SPSS software version 16. Results: The results of this study showed that the prevalence of carotid artery stenosis in patients with stroke is 40.3% and having a history of myocardial infarction (MI) is the only factor associated with an increase in the incidence of carotid artery stenosis in patients with ischemic CVA, and there is no relationship between different risk factors for cardiovascular diseases such as diabetes, hypertension, ischemic heart disease, cigarette smoking, previous CVA, previous transient ischemic attack, and hyperlipidemia and carotid artery stenosis. Conclusion: Patients with a history of MI have a higher incidence of carotid artery stenosis and heart attack as a risk factor for stroke